Studi Kualitatif Penggunaan QRIS (Quick Respond Indonesian Standard) dalam Pemungutan ZIS (Zakat, Infaq, dan Shadaqah) - Gilang Rizaldi; Henri Agustin (Universitas Negeri Padang, 2023)
Research has been carried out on the use of the Indonesian Quick Response Code system as a means to facilitate the collection of zakat, infaq, and alms activities at several mosques in the city of Padang. This study uses a qualitative research method with a descriptive approach. The object of this research is the Indonesian Quick Response Code payment system, while the research subject is the welfare board or mosque general treasurer who plays an important role in implementing the Indonesian Quick Response Code payment system. The methods used in data collection are the interview method and the documentation method. Based on research data, the effectiveness of the basis for using the Indonesian Quick Response Code in collecting zakat, infaq, and alms is assessed based on the application of stakeholder theory and management theory. On the other hand, the obstacles found in this study are that some mosque worshipers do not understand and are accustomed to following technological developments so that pilgrims are more comfortable using the infaq box compared to the Indonesian Quick Response Code system. The limitations of this study are that the research sample is only 5 mosques in the city of Padang, so that further research is expected to be able to take a larger sample.